Rivaroxaban treatment for cancer-associated venous thromboembolism in a patient with heparin-induced thrombocytopenia: a case report - Le, Ke-Jia; Yan, Yi-Dan; Liu, Yang-Xi; Xu, Jia-Bo; Cui, Min; Gu, Zhi-Chun (Translational Cancer Research, 2019)
Low molecular weight heparin (LMWH) is the first-line therapy in acute cancer-associated venous thromboembolism (CAT). However, heparin-induced thrombocytopenia (HIT) is a life-threatening adverse drug reaction that occurs in anticoagulation therapy with LMWH. This article reports the case of a 66-year-old Chinese male who received nadroparin 4100IU twice daily for treating CAT. Unfortunately, the epistaxis persisted and the blood count examination revealed serious thrombocytopenia on postoperative day 5. The patient was diagnosed with HIT and thereafter LMWH therapy was replaced with rivaroxaban. During three months follow-up, the patient had a good recovery without recurrent CAT or bleeding.